SYNTHESIS AND MICROBIOLOGICAL EVALUATION OF ACETYLENIC AMINO ALCOHOLS N-PHENYL CARBAMATE DERIVATIVES - Kassymova M.К.; Nauryzbayev M.K.; Mamyrbekova Aizhan; Mamitova А.D.; Mamyrbekova Aigul; Olga N. Chechina (Academic Scientific Journal of Chemistry, 2019)
The paper presents the results of synthesizing of acetylenic amino alcohols N-phenyl carbamate derivatives and the microbiological evaluation of the latter has been studied. The following microorganisms were considered as objects of microbiological research: Bacillus subtilis, Botrytis cinerea, Echerchia coli, Ervinia caratovorum, Candida albicans, Fusarum solani и Helminthosporium. There were researched physicochemical and bactericidal properties of acetylenic amino alcohols N-phenyl carbamate derivatives. The output of carbamates depends on the content and structure of acetylenic amino alcohols and is 68-88%. The purity, identification and structure of the compounds obtained been has determined by thin-layer and gas-liquid chromatography, elemental analysis, IR (Infrared) and PMR (Proton Magnetic Resonance) spectroscopy. It established that these compounds exhibit high antimicrobial activity against the causative agents of certain animal and plant diseases. The relatively high microbiological activity of the phenylcarbamates studied is associated with the presence of various functional groups in the composition of the molecules.